MENAKAR KEMAMPUAN BERPIKIR TINGKAT TINGGI CALON GURU MATEMATIKA MELALUI LEVEL HOTS MARZANO - Ega Gradini; Firmansyah Firmansyah; Julia Noviani (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2018)
This paper aims to measure students' high-level thinking skills through the level of pre-service mathematics teachers. The author used the Marzano HOTS level which is divided into five dimensions of thinking ability; (1) decision making, (2) problem solving, (3) error analysis, (4) abstraction, and (5) perspective analysis and classification. The instrument used was adapted from Marzano Rubrics for Specific Tasks or Situations (1993). This research is a quantitative research that involved 53 students of the Mathematics Education Department, STAIN Gajah Putih. The results of the study indicate that the ability to think on high-level of the pre-service teacher is at the moderate and low levels.